Evaluasi Status Keberlanjutan Pengelolaan Sumberdaya Ekowisata Mangrove - Melo, Ramla Hartini; Alfin, Edward; Kuvaini, Aang; Nurfaika, Nurfaika; Hendra, Hendra (Indonesian Journal of Conservation, 2023)
Mangrove ecotourism resources in East Pentadu Village, Boalemo Regency are currently still being improved to improve the quality of service. By considering environmental sustainability, management of mangrove ecotourism resources must be based on applicable rules and laws, where mangrove ecotourism services must prioritize the potential of the mangrove forest resources themselves. The aim of this research is to evaluate the condition of the sustainability status of mangrove ecotourism resource management, using a multi-dimensional scaling (MDS) method approach. The current condition of mangrove ecotourism resource management is at a less sustainable status, where the ecological and economic dimensions are less sustainable and need to be intervened by raising the less sustainable status to be quite sustainable or sustainable, the social dimension is at a quite sustainable level.